Preparation of Fecal Microbiota Transplantation Products for Companion Animals - Nina K. Randolph; Matthew Salerno; Hannah Klein; Dubraska Diaz-Campos; Joany C. van Balen; Jenessa A. Winston (PLoS ONE, 2025)
Fecal microbiota transplantation (FMT) is increasingly utilized in small animal medicine for the treatment of a variety of gastrointestinal and non-gastrointestinal disorders. Despite proven clinical efficacy, there is no detailed protocol available for the preparation and storage of FMT products for veterinarians in a variety of clinical settings. Herein, the effect of processing technique on the microbial community structure was assessed with amplicon sequence analysis. Microbial viability was assessed with standard culture techniques using selective media. Given the fastidious nature of many intestinal microbes, colony forming units are considered surrogate viable microbes, representing a portion of potentially viable microbes. FMT products from four screened canine fecal donors and six screened feline fecal donors were processed aerobically according to a double centrifugation protocol adapted from the human medical literature. Fresh feces from an additional three screened canine fecal donors were used to evaluate the effect of cryopreservative, centrifugation, and short-term storage on microbial community structure and in vitro surrogate bacterial viability. Finally, fresh feces from a third group of three screened canine and three screened feline fecal donors were used to evaluate the long-term in vitro surrogate bacterial viability of three frozen and lyophilized FMT products. Microbiota analysis revealed that each canine fecal donor has a unique microbial profile. Processing of canine and feline feces for FMT does not significantly alter the overall microbial community structure. The addition of cryopreservatives and lyopreservatives significantly improved long-term viability, up to 6 months, for frozen and lyophilized FMT products compared to unprocessed raw feces with no cryopreservative. These results prove the practicality of this approach for FMT preparation in veterinary medicine and provide a detailed protocol for researchers and companion animal practitioners. Future in vivo research is needed to evaluate how the preparation and microbial viability of FMT impacts the recipient’s microbial community and clinical outcomes across multiple disease phenotypes.